2017
DOI: 10.1097/wnr.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expression of Ski after rat spinal cord injury

Abstract: Ski is an evolutionarily conserved protein and widely participates in the regulation of various pathological and physiological processes such as wound healing, liver regeneration, development of the embryonic nervous system, muscle differentiation, and progression of many kinds of tumors. However, the distribution and function of Ski in central nervous system lesion and disease remain unclear. In this study, we investigated the spatiotemporal expression of Ski in a spinal cord injury (SCI) model in adult rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 167 In rats with a spinal cord injury, Ski is upregulated in reactive astrocytes, but not in neurons. 187 The inhibition of Smad1 and Smad2 by Ski induces the expression of some neural markers; 188 whereas, Ski -KO mice exhibit reduced expression of nestin, an intermediate filament protein of neuroepithelial cells and myocytes precursors; 189 , 190 embryos of Ski -KO mice also exhibit extra vestigial-digits. 190 Ski appears to maintain the identity of callosal neurons in the developing neurocortex by blocking Ctip2 gene expression through a Ski/Stab2/HDAC1 complex.…”
Section: Role Of Ski and Snon In Development And Tissue Homeostasismentioning
confidence: 99%
“… 167 In rats with a spinal cord injury, Ski is upregulated in reactive astrocytes, but not in neurons. 187 The inhibition of Smad1 and Smad2 by Ski induces the expression of some neural markers; 188 whereas, Ski -KO mice exhibit reduced expression of nestin, an intermediate filament protein of neuroepithelial cells and myocytes precursors; 189 , 190 embryos of Ski -KO mice also exhibit extra vestigial-digits. 190 Ski appears to maintain the identity of callosal neurons in the developing neurocortex by blocking Ctip2 gene expression through a Ski/Stab2/HDAC1 complex.…”
Section: Role Of Ski and Snon In Development And Tissue Homeostasismentioning
confidence: 99%
“…These studies have demonstrated that Ski also plays an important role in the physiological and pathological processes of the central nervous system. In a previous study by our group, we found that Ski was signi cantly upregulated after spinal cord injury and showed a signi cant positive correlation with the expression of the astrocyte-speci c molecule Gfap [32], which suggests that Ski may be a novel molecule regulating astrocyte activation after spinal cord injury. In further in vitro experiments, it was found that intervention of Ski expression by lentiviral knockdown and overexpression could signi cantly affect the proliferation and migration of activated astrocytes [33][34][35][36].…”
Section: Introductionmentioning
confidence: 67%
“…In the course of subsequent studies, researchers also found that Ski plays a key role in regulating the activation and proliferation of broblasts as well as broma cells [50][51][52]. In a previous study by our group, we found that Ski was signi cantly upregulated in rat spinal cord and activated astrocytes after spinal cord injury [32]. In vitro, intervention of Ski expression by knockdown and overexpression can signi cantly affect the proliferation and migration of astrocytes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, Ski has been implicated to involve in many cellular process. 19 Our previous studies have demonstrated that Ski was strikingly up-regulated in reactive astrocytes after spinal cord injury in vivo, 20 and knockdown of Ski arrested astrocytes' cell cycle process and decreased cell proliferation in vitro. 21 However, the accurate mechanism of Ski regulating astrogliosis remains further to be elucidated.…”
Section: Introductionmentioning
confidence: 97%